Three words for goodbye : a novel - Gaynor, Hazel; Webb, Heather, 1976 December 30- (William Morrow, an imprint of HarperCollinsPublishers, 2021)
Two estranged sisters fulfill their dying grandmother's final wish by traveling across Europe and delivering three goodbye letters to those who she has not seen since traveling to Europe four decades earlier.